The effect of early COVID-19 treatment with convalescent plasma on antibody responses to SARS-CoV-2 - Andy Kwan Pui Chan; San Suwanmanee; Arturo Casadevall; Shmuel Shoham; Evan M. Bloch; Kelly A. Gebo; Aaron A. R. Tobian; Andrew Pekosz; Sabra L. Klein; David Sullivan; Diane E. Griffin (Microbiology Spectrum)
ABSTRACT At the COVID-19 pandemic onset, convalescent plasma, collected from patients recovered from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, emerged as a potential treatment option, but the effect on the patient immune response was unclear. To determine treatment effect on the infection antibody response, plasma samples were collected through 90 days from 104 SARS-CoV-2-infected participants after receiving CCP or control plasma, as part of a multicenter, double-blind, randomized, controlled early treatment trial. Enzyme immunoassay (EIA) was used to quantify binding IgG, IgA, and IgM to nucleocapsid (N) protein and IgG to the USA-WA1/2020 spike (S) protein. Avidity assessed antibody maturation. CCP transfusion boosted post-transfusion plasma levels of N-specific IgG, but not IgA or IgM and had a lesser effect on S-specific IgG. Over the first 2 weeks, both trial arm groups generated IgM, IgA, and IgG to N and IgG to S with comparable levels at 14–90 days after transfusion. Levels of IgM and IgA subsequently declined, while IgG was maintained through day 90 for both interventions. Avidity of N-specific IgG increased steadily over the 3-month follow-up in both groups, but S-specific IgG avidity improved only for those in the CCP group. Improved antibody titer correlated with improved avidity over time in both groups. Antibody levels and avidity between early ves late transfusion from symptom onset by trial arm intervention were also similar. In summary, CCP administration had no negative effects on the humoral response to SARS-CoV-2 infection and was associated with qualitatively improved antibodies with higher avidity.IMPORTANCEMonoclonal antibody infusion prevented COVID-19 hospitalizations. However, the massive monoclonal antibody dose, near 7% of total circulating antibodies, has been shown to decrease patient generation of SARS-CoV-2 specific IgM and lower responses to vaccination, possibly by decreasing generation of high avidity neutralization epitopes near the monoclonal binding epitope. We characterized diverse antibody population quality and quantity among intervention groups in the polyclonal COVID-19 convalescent plasma (CCP) randomized control trial, effective in reducing hospitalizations by more than 50% in all participants and 80% in those receiving transfusions with symptom onset before 5 days. Importantly, we observed a greater anti-nucleocapsid compared to anti-Spike antibody level immediately after transfusion. CCP compared to controls did not alter IgG, IgA, or IgM to nucleocapsid or IgG-spike. CCP was associated with greater IgG-nucleocapsid and, to a lesser extent, IgG-spike avidity maturation over follow-up compared to control. CCP transfusions lacked negative effects on antibody levels and avidity.